HUBUNGAN INTERNET TERHADAP PENGELUARAN PENDUDUK DAN TINGKAT KEMISKINAN DI SUMATERA SELATAN - Juairiyah, Oktaf; Yesi, Desri; Aprianti, Nabila; Lamazi, Lamazi (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Nowadays people cannot be separated from the use of the internet as a means of communication which is a daily necessity. This study aims to examine the relationship between population expenditure and poverty levels with internet use in districts / cities in South Sumatra Province. This research is cross sectional with descriptive statistical analysis approach to internet users, population expenditure and poverty levels. There is a relationship that the use of the internet for the purpose of buying / selling goods / services is included in per capita expenditure per person in regencies / cities in South Sumatra with the R square value obtained is 0.5969